THE INFLUENCE OF WORK INCENTIVES AND SOCIAL SECURITY ON IMPROVING EMPLOYEE PERFORMANCE IN REGIONAL PUBLIC COMPANIES TIRTA JENEBERANG DRINKING WATER REGION, GOWA REGENCY - Indriani Dwi Cahyono; Andi Rizfan Rizaldi; M. Yusuf Alfian Rendra Anggoro (International Journal of Economic Research and Financial Accounting, 2024)
This research aims to analyze the effect of incentives and social security on improving employee performance at PDAM Tirta Jeneberang, Gowa Regency. The research method used is quantitative with a descriptive approach. The research location was carried out at PDAM Tirta Jeneberang, Gowa Regency, over a 3 month period. Data was collected through questionnaires and analyzed using descriptive statistical methods via applicationsStatistical Package for the Social Science (SPSS) 25. The results obtained from this research show that there is a positive relationship between Work Incentives (X1) and increased employee performance (Y), as well as Social Security (X2) which contributes positively to increased employee performance (Y) at PDAM Tirta Jeneberang Regency Gowa.